IMPLEMENTASI FUNGSI PENGAWASAN DALAM MENINGKATKAN EFEKTIFITAS PELAYANAN ADMINISTRASI DI KANTOR KECAMATAN NAMOHALU ESIWA KABUPATEN NIAS UTARA - Kurniaman Harefa; Eliagus Telaumbanua; Yamolala Zega; Robin Markus Putra Waruwu (Jurnal Publikasi Manajemen Informatika, 2026)
This research aims to analyze the implementation of the supervisory function in improving the effectiveness of administrative services at the Namohalu Esiwa District Office, North Nias Regency. The research uses a qualitative descriptive approach with data collection techniques through interviews, observation and documentation. Informants consisted of district office leaders and staff. The research results show that the effectiveness of administrative services is not optimal, in terms of speed, accuracy, availability of information and clarity of procedures. The main weakness lies in the suboptimal supervision function, especially continuous and preventive supervision. Apart from that, limited human resources, infrastructure and minimal use of technology also affect service quality. This research concludes that strengthening the supervisory function that is integrated with work systems and information technology is very necessary to increase the effectiveness of administrative services.